Innovative Protocols in the Catalytic Oxidation of 5-Hydroxymethylfurfural - Su, Ting; Zhao, Deyang; Wang, Yantao; Lü, Hongying; Varma, Rajender S; Len, Christophe (ChemSusChem, 2021)
5-Hydroxymethylfurfural (HMF) has been identified as one of the most promising biomass-based multi-purpose platform molecules. Innovative protocols, namely electrocatalysis, photocatalysis, and microwave (MW)-assisted chemistry, as well as continuous-flow systems, add a new dimension and another promising toolbox for the oxidation of HMF in recent years. This Minireview deals with recent progress in the catalytic oxidation of HMF to 2,5-furandicarboxylic acid (FDCA) and other intermediates using noble, non-noble, and metal-free systems deploying emerging protocols. Selective HMF downstream oxidation products could be obtained not only via common catalyst modifications, namely nature of the metal, preparative method, and the property of deployed support, but also by using innovative processes.
Keywords: oxidation; 5-hydroxymethylfurfural; alternative technology; 2,5-furandicarboxylic acid; biomass